Significance of Phallic Complex in the Classification of Indian Pyrgomorphidae (Orthoptera: Pyrgomorphoidea) - Kumar, Hirdesh; Usmani, Mohd. Kamil; Rafi, Uzma; Kumari, Reenu (Journal of the Bombay Natural History Society (JBNHS), 2013)
A study of phallic complex - internal genitalic structures in males - was undertaken in twelve species of grasshoppers, representing six genera under four tribes of the family Pyrgomorphidae. The study revealed that the shape of epiphallus, presence and absence of ancorae, direction of lophi, and comparative size of central membrane of cingulum are stable characters in the identification, and are of significance at each and every taxonomic level. The species studied are arranged under their respective tribes, along with keys to their tribes and genera.